Designing and Building of an Experimental System for Monitoring and Controlling - Masalmeh, Noureddine; Itbaish, Qais (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2012)
This project responds to local environmental problems resulting alocal galvanization industry , it aims at designing and building an adsorption process unilizing a suitable local adsorbent.
CD , no of pages 68,26815, ميكانيك 2/2013 , in the store
Keywords: Monitoring and Controlling; systems